BCL7A‐containing SWI/SNF/BAF complexes modulate mitochondrial bioenergetics during neural progenitor differentiation. (28th October 2022) - Wischhof, Lena; Lee, Hang‐Mao; Tutas, Janine; Overkott, Clemens; Tedt, Eileen; Stork, Miriam; Peitz, Michael; Brüstle, Oliver; Ulas, Thomas; Händler, Kristian; Schultze, Joachim L; Ehninger, Dan; et al.
Abstract: Mammalian SWI/SNF/BAF chromatin remodeling complexes influence cell lineage determination. While the contribution of these complexes to neural progenitor cell (NPC) proliferation and differentiation has been reported, little is known about the transcriptional profiles that determine neurogenesis or gliogenesis. Here, we report that BCL7A is a modulator of the SWI/SNF/BAF complex that stimulates the genome‐wide occupancy of the ATPase subunit BRG1. We demonstrate that BCL7A is dispensable for SWI/SNF/BAF complex integrity, whereas it is essential to regulate Notch/Wnt pathway signaling and mitochondrial bioenergetics in differentiating NPCs. Pharmacological stimulation of Wnt signaling restores mitochondrial respiration and attenuates the defective neurogenic patterns observed in NPCs lacking BCL7A. Consistently, treatment with an enhancer of mitochondrial biogenesis, pioglitazone, partially restores mitochondrial respiration and stimulates neuronal differentiation of BCL7A‐deficient NPCs. Using conditional BCL7A knockout mice, we reveal that BCL7A expression in NPCs and postmitotic neurons is required for neuronal plasticity and supports behavioral and cognitive performance. Together, our findings define the specific contribution of BCL7A‐containing SWI/SNF/BAF complexes to mitochondria‐driven NPC commitment, thereby providing a better understanding of the cell‐intrinsic transcriptional processes that connect metabolism, neuronal morphogenesis, and cognitive flexibility. Synopsis: How mammalian SWI/SNF/BAF chromatin remodeling complexes transcriptionally mediate their involvement in neurogenesis or gliogenesis is not fully understood. Here, a BCL7A‐containing complex is found to transcriptionally modulate mitochondria‐driven differentiation of neural progenitor cells (NPCs). The SWI/SNF/BAF complex subunit BCL7A is highly expressed in both NPCs and neurons. BCL7A‐containing SWI/SNF/BAF complexes promote transcriptional neurogenic profiles in differentiating NPCs. BCL7A loss skews NPC specification toward glial differentiation in vitro and in vivo . BCL7A promotes neural lineage determination by regulating Notch/Wnt signaling and mitochondrial bioenergetics. BCL7A enhances the genome‐wide occupancy of the ATPase BRG1. Abstract : Neurogenic gene expression and Notch/Wnt signaling in differentiating neural progenitor cells depend on BCL7A‐mediated BRG1 chromatin occupancy.